Sustainable entrepreneurial culture in promoting innovation: a higher education perspective - Eriana Astuty; Ridho Bramulya Ikhsan; Rudy Aryanto (Institute of Advanced Engineering and Science, 2024)
This research aimed to build a quadruple-helix partnership model between universities, government, industry, and community from the higher education (HE) perspective in creating various innovations to support sustainable regional socio-economic development. This study used exploratory quantitative research to develop, predict the model, and explain the empirical evidence. In addition to the model, this study found that institutional sustainable entrepreneurial culture (SEC) could be developed by transforming the university into an entrepreneurial university (EU) and applying sustainable development goals (SDGs) principles to teaching-researching-community service activities, management and governance, and institutional leadership. This study also confirmed that universities with an SEC cannot directly affect the emergence of various innovations sourced from knowledge and research results but must be mediated by internal consensus within academia and external consensus among partnership actors. The research contributions are aimed at: i) HE policymakers who will transform their institutions into EU as a first step in carrying out the university’s third mission; ii) HE will build quadruple helix partnerships; and iii) Micro, small, and medium enterprise (MSME) which will take advantage of the innovations offered in the quadruple-helix. In addition, this research deepens the Etzkowitz partnership path model in which HE, a source of knowledge for innovation, becomes more focused in the form of SDGs-based EU.